Effect of Mannoprotein-Producing Yeast on Viscosity and Mouthfeel of Red Wine - Osorio-Lira, F (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Mannoproteins enhance wine stability and sensory properties, but their specific role in modulating viscosity and mouthfeel across wine quality levels remains underexplored. This study explores the nuanced impact of various mannoprotein-producing yeast strains on specific mouthfeel sensations, particularly emphasizing viscosity, across Standard and Premium quality tiers of Cabernet Sauvignon commercial wines. The aim was to understand the intricate relationship between yeast-derived mannoproteins and the broader sensory landscape of red wines. The methodology encompasses a comprehensive mannose extraction method, rheological measurements, and sensory Rate-All-That-Apply evaluations, all of which are integrated into a Principal Component Analysis. The results showed slight color variations due to the wine spending one month on lees. A positive correlation was found between mannose content and viscosity in only Standard-quality wines. The correlation with sensory data indicated a strong relationship between volume, viscosity, and mannose content in Premium-quality wines, which was less pronounced in Standard-quality wines. Furthermore, parameters related to mouthfeel quality, such as roundness and smoothness, were also associated with these findings. Prospects involve further exploration of correlations between mouthfeel sensations, sensory descriptors, and the structural characteristics of mannoproteins, aiming for a more comprehensive understanding of the intricate interplay in wine composition. © 2025 by the authors.